2012
DOI: 10.1118/1.4745565
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the beam quality index of high‐energy photon beams under nonstandard reference conditions

Hugo Palmans

Abstract: The models proposed here can be used in practical recommendations for the dosimetry of small and nonstandard fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…It was demonstrated by Sauer that this methodology also works well for nonsquare (e.g., circular or rectangular) fields using the equivalent square fields method (BJR Supplement 25) and even for FFF beams after applying a correction for the scatter deficiency caused by their conical‐shape lateral beam profiles (yielding a virtually flattened equivalent square field size). Based on the same approach and the same BJR Supplement 25 data, Palmans derived self‐consistent formulas for the derivation of TPR 20,10 (10) from TPR 20,10 ( S ) for a narrower range of square field sizes ( S between 4 and 12 cm, the relevant range) as well as for the derivation of % dd (10,10) X from % dd (10, S ) X , the percentage depth dose at 10 cm depth in a water phantom due to photons only (i.e., excluding the contribution of electron contamination) for an equivalent square field size of S cm × S cm at a source‐to‐surface distance (SSD) of 100 cm.…”
Section: Physics Of Small‐field Dosimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated by Sauer that this methodology also works well for nonsquare (e.g., circular or rectangular) fields using the equivalent square fields method (BJR Supplement 25) and even for FFF beams after applying a correction for the scatter deficiency caused by their conical‐shape lateral beam profiles (yielding a virtually flattened equivalent square field size). Based on the same approach and the same BJR Supplement 25 data, Palmans derived self‐consistent formulas for the derivation of TPR 20,10 (10) from TPR 20,10 ( S ) for a narrower range of square field sizes ( S between 4 and 12 cm, the relevant range) as well as for the derivation of % dd (10,10) X from % dd (10, S ) X , the percentage depth dose at 10 cm depth in a water phantom due to photons only (i.e., excluding the contribution of electron contamination) for an equivalent square field size of S cm × S cm at a source‐to‐surface distance (SSD) of 100 cm.…”
Section: Physics Of Small‐field Dosimetrymentioning
confidence: 99%
“…For rectangular and circular fields, IAEA TRS‐483 provides tables to derive their equivalent square msr field sizes, including data for generic FFF beams that are also valid for TomoTherapy and CyberKnife machines . The beam quality specifier is then determined as:normalTPR20,10false(10false)=normalTPR20,10false(Sfalse)+c·false(10Sfalse)1+c·(10S),where c = (16.15 ± 0.12) × 10 −3 , or%ddfalse(10,10false)=%dd(10,S)+80c·(10S)1+c·(10S),where c = (53.4 ± 1.1) × 10 −3 . It should be noted that if a field is smaller than 4 cm, it cannot be considered to be an msr field for accelerating potentials of 6 MV or higher.…”
Section: Formalism and Applicationmentioning
confidence: 99%
“…TPR 20,10 (10) or % dd (10,10) are derived from the following equations, valid for 4 cm ≤ S ≤ 12 cm, with S being the equivalent square msr field size:TPR20,10false(10false)=TPR20,10false(Sfalse)+cfalse(10Sfalse)1+c(10S)where c = (16.15 ± 0.12) × 10 −3 , or%ddfalse(10,10false)=%dd(10,S)+80c(10S)1+c(10S)where c = (53.4 ± 1.1) × 10 −3 . These expressions were derived by Palmans . It should be noted that Sauer first proposed a solution for the determination of TPR 20,10 (10) from measured values of TPR 20,10 ( S ) for different field sizes .…”
Section: Overview Of the Formalism For Reference And Relative Dosimetmentioning
confidence: 99%
“…Scott et al [16] have suggested that one set of correction factors could be calculated for a wide range of linacs, despite variations in beam quality with linac type and field size [18] aim of this study was to develop a mathematical relation from experimental data that predicts the magnitude of diode overresponse in a range of linacs. The mathematical relation was validated by comparison with the correction factors available in the literature [5][6][7][8]13,15,14,11].…”
Section: Introductionmentioning
confidence: 99%
“…Scott et al [16] have suggested that one set of correction factors could be calculated for a wide range of linacs, despite variations in beam quality with linac type and field size [18]. The…”
Section: Introductionmentioning
confidence: 99%